2021
DOI: 10.46405/ejms.v3i1.171
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Prescribing Antibiotics among Dental Practitioners in Chitwan

Abstract: Background: Antibiotic resistance in recent years has become a major threat to public health globally. In dental practice, antibiotics and analgesics are commonly used for infection control and management of pain. The knowledge, attitude and practice skills of antibiotic prescription by dental practitioners should be continuously evaluated. The aim of this study was to assess the knowledge, attitude and practice regarding antibiotic prescription among dental practitioners.Methods: A descriptive cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Most dentists in the study prescribed majorly Amoxicillin followed by Amoxicillin-Clavulanic acid antibiotics for non-allergic to penicillin patients. This is agreed by Paude et al (23) . Which may be attributed to that Amoxicillin, together alone and in grouping with clavulanic acid, is considered the drug of first choice for the treatment of dental infections in pediatric patients and adolescents.…”
Section: Mdj Discussionsupporting
confidence: 85%
“…Most dentists in the study prescribed majorly Amoxicillin followed by Amoxicillin-Clavulanic acid antibiotics for non-allergic to penicillin patients. This is agreed by Paude et al (23) . Which may be attributed to that Amoxicillin, together alone and in grouping with clavulanic acid, is considered the drug of first choice for the treatment of dental infections in pediatric patients and adolescents.…”
Section: Mdj Discussionsupporting
confidence: 85%
“…Moreover, these antibiotics should be administered at optimal dosages and treatment durations (19). In comparison to another study where 77% of dentists were aware of antibiotic resistance, this study found a slightly lower awareness rate of 72% (20). Dental practitioners need to recognize the growing challenge of antibiotic resistance, primarily driven by overprescription and misuse.…”
Section: Discussionmentioning
confidence: 75%